TRANSYLVANIAN JOURNAL OF TOURISM AND TERRITORIAL DEVELOPMENT VOLUME 2 / ISSUE 1 - NIȚĂ, Adrian; MAGYARI-SÁSKA, Zsolt; DOMBAY, István (Presa Universitară Clujeană, 2017)
In response to the changes in consumer trends, wine producers mark their wines made using traditional methods. However, in the absence of appropriate controls it is not clear what the consumer can expect from the product. The study focuses on the issue whether it is the size of the plantation, the processing methods, the way of wine sales, the nutritional values of the wine, or the winemaker’s attitude that determines what can be called craft wine. Although there is no consensus, it is typical of the artisan winemakers producing wines to possess expertise in the traditional way, mostly unique hand-made wines associated with the production area. Following the principles of sustainability, quality produce, “artistic” product is created. It is important to give an exact definition, because it could help not only the consumer but also the winemaker too.